End member composition and loadings of silt grain size data of multiple cores from the Eastern Mediterranean Sea - Sarah Beuscher; Werner Ehrmann; Stefan Krüger; Gerhard Schmiedl (PANGAEA, 2019)
The dataset contains silt grain size data of cores SL71, SL99, SL110, SL112, SL114, Sl119, SL123, SL143 and SL148 from the Eastern Mediterranean Sea, measured with a laser particle sizer, as well as the results of end member modelling of these datasets. Age determinations for the unpublished cores SL99, SL114 and SL119 are included.
In: Beuscher, S et al. (2019): End member modelling of silt grain size data of multiple cores from the Eastern Mediterranean Sea [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.898583